Diverse Positions: Theoreticl and Political Contributions on Diversity (Revista Rupturas, 2019)
In this paper, you will find a series of theoretical and political elements for understanding, debate and the study of diversity based on the views of activists, theorists, and theoreticians who have shared their reflections and experiences. The document is organized in eleven sections addressing the following topics: The contributions of the Feminist theory and the concept of the body as a zone of dispute, the pathologization of the body, pathologization and diversity, the pathologization of transsexuality, biopower or biopolitics and their relationship with diverse communities, the acronym LGBTI and its controversy: are they important to define and self-recognize, represent a real inclusion?, definitions according to the international legal framework, discrimination by sex orientation, identity and expression, some ideas about labels and categories of identification of sexual diversity, a section on Eve Kosofsky’s proposal on understanding diversity and a series of final reflections.
Keywords: sexual diversity; LGBT; gender studies; feminism; biopolitics; transsexuality; pathologization; diverse communities